Agronomic response of subsurface versus surface drip irrigation in Nagpur mandarin (Citrus reticulata Blanco) on Indian Vertisol - Meshram, Deodas Tarachand; Srivastava, Anoop Kumar; Thirugnanavel, Anbazhagan; Meshram, Naresh M.; Jagannadham, Prasanth Tej Kumar; Utkhede, Akshay D.; Pangul, Chetan S. (Frontiers in Horticulture, 2025)
IntroductionCitrus is a highly water- and nutrient-demanding crop, with several previous efforts focusing on improving water productivity (WP) and nutrient use efficiency (NUE). However, studies highlighting the performance of subsurface drip irrigation (SDI) versus drip irrigation (DI) in black clay soil (Vertisol) for Nagpur mandarin are limited.MethodsThis study evaluated six treatments: T1 (SDI with double inline laterals at 100 cm radially from the trunk and 30 cm vertically placed into the soil, drippers spaced 30 cm apart); T2 (SDI with double inline laterals at 100 cm radially from the trunk and 30 cm vertically placed into the soil, drippers spaced 40 cm apart); T3 (SDI with double inline laterals at 100 cm radially from the trunk and 30 cm vertically placed into the soil, drippers spaced 50 cm apart); T4 (SDI with double inline laterals at 100 cm radially from the trunk and 30 cm vertically placed into the soil, drippers spaced 60 cm apart); T5 (DI with double online laterals at 100 cm from the trunk with 6 drippers spaced 60 cm apart; control as farmers’ practice); and T6 (DI with ring-type online laterals at 10 cm from the trunk with 12 drippers tree-1 placed 60 cm apart). These treatments were for their effects on growth performance, fruit yield, fruit quality, WP, and leaf nutrient composition.Results and discussionSignificantly higher WP and lower water requirement were observed with SDI (7.96–10.73 kgm-3 and 13,260 L plant-1 year-1) compared with DI treatments (2.79–3.04 kg m-³ and 32,670 L plant-1 year-1). These observations were associated with a 25.29% higher fruit yield in SDI over DI treatments. Similarly, fruit quality parameters, viz., juice content and total soluble solids (TSS), were 6.65% and 1.17°Brix higher, respectively, in SDI than in DI treatments. Consequently, SDI treatments registered higher leaf N, P, K, Ca, Mg, Fe, Mn, and Zn contents by 4.81%, 15.68%, 6.60%, 17.51%, 3.18%, 7.70%, 5.04%, and 15.67%, respectively, over DI treatments. Thus, SDI treatments saved.ConclusionThe T3 treatment was the most effective SDI treatment, registering 47.32% higher fruit yield and 64.87% higher WP than DI treatments, along with significantly improved leaf and fruit nutrient composition.